Bi‐frequency control for LLC resonant converter with fast transient response. Issue 20 (7th September 2016) - Zhong, Shu; Xu, Jianping; Zhao, Sheng; Zhou, Xiang
Abstract : Bi‐frequency (BF) control for LLC resonant converter is proposed and studied. Compared with conventional voltage mode control of LLC resonant converter, which realises output voltage regulation by adjusting control pulse frequency cycle by cycle, BF control of LLC resonant converter realises its output voltage regulation by adjusting the combination of two preset control pulses with 50% duty ratio and different switching frequencies. BF controlled LLC resonant converter benefits from simple controller design and fast transient response. A 130 W prototype is presented to verify the analysis results of BF control method.